The Effect of Anaerobic Exercises Using TRX on the Development of Some Bio-kinetics Capabilities and the Accuracy Index for Handball Players (International Journal of Psychosocial Rehabilitation, 2020)
It depends on the development of the physical abilities or mobility of the handball players that gain muscle strength, and that in turn leads to the production of explosive and rapid strength, as well as the development of accurate aiming, and hence the importance of research using bodyweight exercises through the TRX ropes to know their effect in developing biokinetics and thus develop a handcrafted accuracy index for handball players. The researchers found that, by continuing with the handball march and being former players and current coaches, there is a decrease in the level of motor performance required in some offensive skills, including aiming skill, and this decrease in the level of performance may be due to the shortcomings of some tribal bidynamics in the stages of the motor performance of that skill, which is one of the calculating skills in handball. The research aimed at identifying the effect of training using TRX on developing the biokinetic capabilities of handball and the accuracy index for ball players, and the researchers assume that exercises using TRX have a significant effect in developing some biokinetics with a ball The hand and the accuracy index for handball players: what is the research methodology? The two researchers used the experimental approach in solving the research problem. As for the research community and its sample, it was determined by the handball players' clubs in the province of Najaf, and through the lottery, the researchers chose the Najaf sports club, which has 16 players. Who represent the research community? after excluding the goalkeepers for the privacy of their exercises and the injured players, the number is (4), so the sample number reached (12) players. they were randomly divided by lottery into two equal groups by (6) players in each group (control and experimental). And the researchers reached the results, including that Derbies using the tool TRX influenced positively the development of some capabilities and the biodynamic index shooting accuracy of the handball players.